2022
DOI: 10.1155/2022/7506157
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis and Research on Influencing Factors of College Students’ Satisfaction with Physical Education

Abstract: Physical education is an important part of a university, and the satisfaction of college students for physical education directly determines the teaching effect of physical education. Therefore, it is of great significance to understand college students’ satisfaction with physical education and its influencing factors for improving the level of physical education. In this paper, by means of multistage sampling, probability sampling according to scale and random equidistant sampling, 7 main campuses, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%